The Effect Of Parental Pressure On Learning Motivation Students - Ulfa, Ina; Nurjaman , Asep Rudi (CV. Generasi Insan Rafflesia, 2023)
This study aims to determine the influence of parental pressure on students that is excessive and makes student learning motivation decrease and results in failure in learning. The habit of parents suppresses or forbids their children to be excessive, not allowed to play a lot, which is very influential on student learning motivation because students consider themselves adults and can take care of themselves which is contrary to the assumptions of parents, namely assuming that their children have become students. still a small child and need supervision of course. This research is a descriptive qualitative research. In this study, researchers used data collection with the observation method, and collected data using a question questionnaire.